Knowledge Structure and Trends in Poverty Research on the Web of Science Database: A Bibliometric Analysis - Chansanam, Wirapong; Li, Chunqiu (Journal of Mekong Societies, 2023)
The study of poverty has made significant progress in the last decades. Bibliometric analysis, the most extensively used technique for scientific mapping, has not been widely utilized to explore knowledge structure and trends for poverty research. Based on domain-level and knowledge structure analysis, this study used data from the Web of Science (WoS) database, which included 23,939 published articles from 2011 to 2022 on poverty research. Data analysis and visualization may be accomplished with the bibliometrix package in R, an open-source software. There are several ways that trends can be mapped, such as trend themes, bibliometric coupling, and co-occurrence networks. There has been a 3.58 percent annual growth in poverty research since 2011. Studying the most frequently used terms and phrases in poverty research makes it possible to see which research areas have the greatest impact. According to the results, poverty, COVID-19, India, children, gender, Africa, inequality, health, and food security should be the focus of future research.